Pengaruh Keselamatan dan Kesehatan Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan PT Bahari Internasional Mandiri Medan - Indria, Tika; Julkarnain, Julkarnain; Tarigan, Nur M. Ridha; Putri, Mentari Indah Aprillia (Jurnal Prodi Fakultas Ekonomi-UISU, 2023)
This aim is to find out the Effect of Occupational Safety and Health and Job Satisfaction on Employee Performance at PT Bahari Internasional Mandiri Medan. The sampling technique used is the total sampling method because the population in this company is 51 people. The analysis technique used is descriptive method and quantitative method. The results of this study indicate that the variable occupational safety and health (X1) has a positive and significant effect on the performance of employees of PT. Bahari Internasional Mandiri Medan Job satisfaction variable (X2) has a positive and significant effect on the performance of employees of PT. Bahari Internasional Mandiri Medan and the variables of occupational safety and health and job satisfaction have a positive and significant effect on the performance of employees of PT Bahari International Mandiri Medan.